Process Standardization for the Manufacture of Shrikhand Spread - Sarkar, S.; Sur, A.; Sarkar, K.; Majhi, R.; Chatterjee, K.; Sikder, B.; Basu, S.; Paul, S. (Journal of Nutritional Therapeutics, 2018)
Purpose: Shrikhand Spread, a unique sweetened fermented Indian milk product is made by separation of whey from dahi, the Indian counterpart of Western yoghurt, followed by addition of sugar. Production of dahi employing traditional method involved undefined mixed starter cultures, uncontrolled fermentation and longer production time resulting in wide variation in its chemical and microbiological qualities. In order to cater to a product with desirable properties like lower post-acidification, higher flavour profile, firm body and lower syneresis coupled with shorter production time, conjugated application of yoghurt cultures and dahi cultures were tried. Since the shelf-life of dahi is limited, conversion into shrikhand spread may be used as a tool to extend the shelf-life and therefore the market reach towards commercialization into the global market as a potential functional food. Design/Methodology/Approach: Different batches of dahi were made from homogenized (Stage I - 2500 psi, Stage II - 500 psi) and pasteurized (74-78 °C/16-19 Sec) milk, pre-adjusted to 3.15-3.20% fat and 11.40% snf with diverse starter combinations selected upon the extent of post acidification, volatile acid production, syneresis and rheological characteristics. Homogenized, pasteurized and regulated milk was further subjected to a heat-treatment (90°C/10 min) and seeded with selected starter combinations to obtain firm curd intended for shrikhand spread manufacture. Shelf-life of shrikhand spread was evaluated in terms of chemical and microbiological criteria upto 7 days of storage at 8±1°C. Findings: Starter combination of eXactDahi 2+YoFlex Express 1.0 at an incubation temperature-time combination of 45°C/5h was found most suitable for producing dahi with smooth body, higher volatile acidity and low syneresis. Utilization of dahi obtained employing the above starter combination for the manufacture shrikhand spread was suggested and the product was found to retain its goodness when stored for 7 days at 8±1°C. Originality/Value: Conjugated use of yoghurt cultures with dahi cultures was suggested to overcome the drawbacks of traditional process of dahi manufacture suitable for conversion into shrikhand spread. This dahi was found capable of enhancing its dietetic value in addition.